Optimalisasi Pelayanan Publik di Balai Pendidikan & Pelatihan Keagamaan Papua - Manga’pan, Yotan; Saa, Septinus (JURNAL EKOLOGI BIROKRASI, 2025)
The Papua Religious Education and Training Center plays an important role in developing the competence of the State Civil Apparatus based on Law Number 20 of 2023 concerning the State Civil Apparatus. There are many challenges faced in various improvements in public services, including problems related to training program planning, availability of infrastructure and limited budgets. If these obstacles are not managed well, they will have a negative impact on the State Civil Apparatus performance. This research aims to analyze superior public services, supporting and inhibiting factors and recommend models for optimizing superior public services at the Papua Religious Education and Training Center. Through the literature study method, we found that: Tangibles or physical evidence still needs to be completed. Reliability of human resources, training facilities, consumption services for participants and post-training services need to be improved; Responsiveness is quite good; Assurance and certainty of employee capabilities continues to be improved; Empathy is good. Supporting factors such as competent human resources, effective management systems, collaboration with stakeholders, and advanced information and communication technology, will improve the quality of the State Civil Apparatus and their performance; Inhibiting factors such as budget limitations, lack of facilities and infrastructure, as well as cultural differences in the Papuan context, can interfere with improving service quality. The superior public service optimization model that can be implemented at the Papua Religious Education and Training Center is: Building physical facilities, increasing human resources and training facilities, increasing responsiveness, regular monitoring and evaluation, and increasing output by holding training in district/city areas.